Application of cellular microstructural diffusion MRI (cell size imaging) in rectal lesions: a preliminary study - Kou, Peisi; Lin, Liangjie; Li, Ying; Qin, Hui; Zhang, Kun; Zhang, Wenhua; Li, Juan; Zhang, Yong; Cheng, Jingliang (Frontiers in Oncology, 2025)
ObjectivesTo explore the value of cellular microstructural mapping by IMPULSED (imaging microstructural parameters using limited spectrally edited diffusion) method in evaluating the histological type and prognostic factors of rectal lesions.Materials and methodsSixty-six patients with rectal lesions were enrolled in this study. All subjects underwent MRI scans including conventional diffusion weighted imaging (DWI) and the IMPULSED MRI scans of oscillating gradient spin-echo (OGSE) and pulse gradient spin-echo (PGSE) sequences. Parameters including mean cell diameter (dmean), intracellular fraction (vin), extracellular diffusivity (dex), cellularity, and apparent diffusion coefficient (ADC) values (ADCPGSE, ADC17Hz, ADC33Hz, and ADC of conventional DWI) were measured in different histopathologic types, grades, stages, and structure invasion statuses. The receiver operating characteristic (ROC) curve analysis was used to evaluate diagnostic power. The sensitivity, specificity, and the corresponding area under the curves (AUCs) were calculated.ResultsOur preliminary results illustrated that malignant lesion showed higher vin and cellularity ([0.2867 ± 0.0697] vs. [0.1856 ± 0.1011], [2.3508 ± 0.6055] vs. [1.2716 ± 0.4574], all P<0.05), lower dex and ADC values (ADCPGSE, ADC17Hz, and ADC of conventional DWI) compared to benign lesion ([2.1637 ± 0.3303 μm2/ms] vs. [2.5595 ± 0.5085 μm2/ms], [0.9238 (0.7959, 1.0741) ×10-3 mm2/s] vs. [1.3373 ± 0.3902×10-3 mm2/s], [1.3204 ± 0.2342×10-3 mm2/s] vs. [1.8029 ± 0.3119×10-3 mm2/s], [0.7400 (0.6750, 0.8375) ×10-3 mm2/s] vs. [1.0550 ± 1.1191×10-3 mm2/s], all P<0.05), while no significant difference was seen for dmean. Vin and cellularity of rectal common adenocarcinoma (AC) were significantly higher than those of rectal mucinous adenocarcinoma (MC) ([0.2994 ± 0.0626] vs. [0.2028 ± 0.0571], [2.4579 ± 0.5553] vs. [1.6412 ± 0.4347], all P<0.05), while dex and ADC values (ADCPGSE, ADC17Hz, ADC33Hz, and ADC of conventional DWI) were lower in AC ([2.1189 ± 0.3187 μm2/ms] vs. [2.4609 ± 0.2534 μm2/ms], [0.8996 ± 0.1583×10-3 mm2/s] vs. [1.2072 ± 0.2326×10-3 mm2/s], [1.2714 ± 0.1916×10-3 mm2/s] vs. [1.6451 ± 0.2420×10-3 mm2/s], [1.8963 (1.6481, 2.1138) ×10-3 mm2/s] vs. [2.3104 ± 0.3851×10-3 mm2/s], [0.7341 ± 0.8872×10-3 mm2/s] vs. [1.1410 ± 0.1840×10-3 mm2/s], all P<0.05). In AC group, the dmean had significant difference between negative and positive tumor budding (TB) ([13.2590 ± 1.3255 μm] vs. [14.3014 ± 1.1830 μm], P<0.05). No significant difference of dmean, vin, dex, cellularity or ADC values was observed in AC with different grade, T stage, N stage, perineural and lymphovascular invasion (all P>0.05). The ROC curves showed that the area under the curves (AUCs) of vin, dex, cellularity, and ADC values (ADCPGSE, ADC17Hz, and ADC of conventional DWI) for distinguishing malignant and benign lesion were 0.803, 0.757, 0.948, 0.807, 0.908 and 0.905, respectively. The AUCs of vin, dex, cellularity, and ADC values (ADCPGSE, ADC17Hz, ADC33Hz, and ADC of conventional DWI) in distinguishing AC from MC were 0.887, 0.802, 0.906, 0.896, 0.896, 0.781 and 0.991, respectively. The AUC of the dmean for evaluating TB status was 0.726. The AUC of ADC from conventional DWI for evaluating WHO grade was 0.739.ConclusionCellular microstructural mapping by the IMPULSED method has great potential in preoperative evaluation of rectal lesions. It could be helpful in differentiating malignant and benign lesions, distinguishing AC from MC, and in predicting the TB status.